The political challenges of deep decarbonisation: towards a more integrated agenda - Jordan, Andrew J.; Lorenzoni, Irene; Tosun, Jale; Enguer, Joan; Geese, Lucas; Kenny, John; Levario Saad, Emiliano; Moore, Brendan; Schaub, Simon G. (Climate action, 2022)
Adopting public policies to deliver the ambitious long-term goals of the Paris Agreement will require significant societal commitment. That commitment will eventually emerge from the interaction between policies, publics and politicians. This article has two main aims. First, it reviews the existing literatures on these three to identify salient research gaps. It finds that existing work has focused on one aspect rather than the dynamic interactions between them all. Second, it sets out a more integrated research agenda that explores the three-way interaction between publics, policies and politicians. It reveals that greater integration is required to understand better the conditions under which different political systems address societal commitment dilemmas. In the absence of greater research integration, there is a risk that policymakers cling to two prominent but partial policy prescriptions: that ‘democracy’ itself is the problem and should be suspended; and that more deliberative forms of democracy are required without explaining how they will co-exist with existing forms.
Gesehen am 12.07.2023